Security of encrypted database in the cloud - H.Sulaiman, Yousif (International Journal of Engineering and Technology, 2018)
Existing encryption techniques ensure or safeness, either effectiveness, but not both. most circuits even show the order of cipher tupelos , that allow opponents to accurately estimate the plain text values. This paper present -tree, hierarchic cipher index, which can be safely located in a cloud and effectively distorted. It is based on the arrangement, which was designed for cipher requests using the encryption method Ðsymmetrical scalar produce handling encryption (ASPE).Â Â
Keywords: Query Encryption; Database Encryption; Cloud Computing; Hierarchical Index.